2014 Sixth International Workshop on Quality of Multimedia Experience (QoMEX) 2014
DOI: 10.1109/qomex.2014.6982280
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric delay in video-mediated group discussions

Abstract: Delay has been found as one of the most crucial factors determining the Quality of Experience (QoE) in synchronous video-mediated communication. The effect has been extensively studied for dyadic conversations and recently the study of small group communications has become the focus of the research community. Contrary to dyads, in which the delay is symmetrically perceived, this is not the case for groups. Due to the heterogeneous structure of the internet asymmetric delays between participants are likely to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…It is known that the interactivity (e.g. amount speaker changes) aggravates the effect of delay [19][20] [21]. There are also indications that in cases of double talk higher audio quality improves the experience [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the interactivity (e.g. amount speaker changes) aggravates the effect of delay [19][20] [21]. There are also indications that in cases of double talk higher audio quality improves the experience [22].…”
Section: Discussionmentioning
confidence: 99%
“…We already reported about the investigation of asymmetric delay conditions and general differences between asymmetric, symmetric and dyadic setups [12]. In this paper we make a more fine-grained analysis user interactivity taking into account role-theory as well.…”
Section: Introductionmentioning
confidence: 99%
“…This testbed was subsequently used in a number of studies. In [5], the impact of asymmetric delay on QoE was investigated for multi-party telemeetings. The study findings confirmed the assumed negative impact of asymmetric delay: if a delay of more than 500 ms is introduced for only one participant, this has a severe negative impact on the QoE of the whole group.…”
Section: Related Workmentioning
confidence: 99%
“…The messages of sender and receiver (audio and video input) need to be recorded, prepared and encoded for transmission, transmitted over a network, decoded by the receiving device and finally presented to the other party [5]. During each of these steps, delay and additional technical artefacts that may impact the produced and experienced audio and video quality, as well as the synchronisation between both modalities [6] may be introduced.…”
Section: Introductionmentioning
confidence: 99%